Pengaruh Ideologi Visual dalam Penciptaan Positioning Clothing (Studi Kasus: Unkl/347-Bandung) - Hartanti, Monica (Institute of Research and Community Outreach - Petra Christian University, 2012)
The Uniqueness and characteristics of Clothing, two of the fashion categories have created the underÂ¬standing of fashion as an ideology, which ensures the functioning of dominant and dominance systems in a social order. Through the analysis of qualitative descriptive research will be known the visual ideology of a clothing product formed by producers in the eyes of consumers. In the end it is capable of forming the product positioning concerned. The results of of this research reveals the emergence of Ideology in clothing, based on the ideals of the creator of the clothing products. The formation of these ideals cannot be separated from the role of the community as a medium that supports the absorption of the ideology as the characteristic of a particular group. It reveals that visual ideology is one of the important factors that establishes the positioning of a product, which is created because of the existence of product differentiation that supports it.